Galleria mellonella as an experimental model for studying periodontopathogens - Santos, Thaís Aguiar [UNESP]; Scorzoni, Liliana [UNESP]; Santos, Aline de Castro [UNESP]; Junqueira, Juliana Campos [UNESP]; Anbinder, Ana Lia [UNESP] (Wolters Kluwer, 2020)
In the present study, Galleria mellonella was evaluated as a potential infection model for periodontal bacteria, more specifically, Porphyromonas gingivalis, Fusobacterium nucleatum, and Aggregatibacter actinomycetemcomitans. All the bacteria evaluated were pathogenic to G. mellonella, causing their death in a concentration-dependent manner, and a decrease in their hemocyte count. Moreover, it was possible to recover the bacteria from the larvae hemolymph and determine the colony-forming units per larvae. G. mellonella is an effective model that may help to better understand the host-microbe interactions in periodontics.
Keywords: Aggregatibacter actinomycetemcomitans; Fusobacterium nucleatum; Galleria mellonella; Periodontal diseases; Porphyromonas gingivalis